2020
DOI: 10.18280/ijdne.150601
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Applicability of Green Building Information Modelling for Existing Green Buildings

Abstract: Green Building Information Modelling is a novel approach which address the momentous need of sustainability. It offers more standardized way of creating buildings which in turn optimize the building performances while attending to the sustainable requirements. Comprising numerous techniques, Green BIM ensures more accurate and comprehensive building performances to optimize the energy efficiency of buildings. Thus, there is a considerable advantage to create more energy efficient buildings using Green BIM. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A significant number of scientific and practical works [18][19][20][21] focus on the state level of green development on environmental protection while forgetting about the work of ordinary lawyers and legal teams, who jointly counteract a significant number of local threats.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of scientific and practical works [18][19][20][21] focus on the state level of green development on environmental protection while forgetting about the work of ordinary lawyers and legal teams, who jointly counteract a significant number of local threats.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al [16] analyzed the efficiency of a high-rise residential building in Hong Kong through the interoperability between BIM and BES, using Revit and DesignBuilder stemming from the exportation with the gbxml format, and concluded that there was a loss of data between them. Rathnasiri et al [17] analyzed building sustainability based on the GreenBIM method, which approaches three topics, sustainable design, BIM, and building performance, through BIM/BES interoperability (Revit 2017 and GBS) in the case study of an existing building. The authors concluded that BIM/BES interoperability is flawed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a context in which the construction industry represents one of the sectors most responsible for global carbon emissions [28], learning how to design sustainable buildings is essential [29,30]. BIM could be the key to revolutionizing the entire construction industry, leading to a substantial reduction in its environmental impact [31,32]. In fact, this technology is able to support the designer in managing the characteristics of a building during the entire design and construction process, facilitating, for example, the prediction of the exact quantity of materials needed during the construction phase, the management of waste during the demolition phase, and the choice of energy-efficient design solutions during the design phase.…”
Section: Bim-based Analyses For the Design Of Green Buildingsmentioning
confidence: 99%